Assessment of Community-Based Systems Monitoring Household Welfare - Isabelita Z. Alba; Celia M. Reyes (Philippine Institute for Development Studies (PIDS), 1994)
The analysis of micro impacts of macroeconomic adjustment policies (MIMAP) is a relatively new discipline. It has spawned out of the concern that adjustment policies aimed to correct macroeconomic imbalances have adverse impacts to vulnerable sectors. This paper seeks to make an inventory and an evaluation of existing and proposed community-based monitoring systems. It also tries to list MIMAP indicators, to identify potential monitors at the barangay and municipal levels and to specify a scheme to institutionalize this monitoring system.
Keywords: 330; vulnerable groups; rural sector; MIMAP